2022
DOI: 10.3390/land11091477
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Characteristics and Influencing Factors of Basic Public Service Levels in the Yangtze River Delta Region, China

Abstract: Basic public services are essential to ensure regional social equity and promote regional integrated development. As the Yangtze River Delta region (YRDR) is an example of integrated regional development in China, the integration of basic public services plays a crucial role in promoting regions’ integrated development. However, little studies provide evidence of the characteristics and influencing factors of basic public services in the YRDR. Taking the YRDR as the study area, this paper constructed a compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…At present, researches on inter-city patent cooperation are mostly focused on the Yangtze River Delta and the Guangdong-Hong Kong-Macao Greater Bay Area. For example, Curley [21] found that the number of inter-city cooperative patents in the Yangtze River Delta region is related to time, cultural proximity between cities, geographical proximity between cities, and proximity of urban innovation capacity. Patent cooperation tends to concentrate on the regions with large patent output; Zhang Ruofan [22] found that the inter-city cooperation network of the Guangdong-Hong Kong-Macao Greater Bay Area presented a significant marginal core structure.…”
Section: Inter-city Patent Cooperation In Beijing-tianjin-hebei Regionmentioning
confidence: 99%
“…At present, researches on inter-city patent cooperation are mostly focused on the Yangtze River Delta and the Guangdong-Hong Kong-Macao Greater Bay Area. For example, Curley [21] found that the number of inter-city cooperative patents in the Yangtze River Delta region is related to time, cultural proximity between cities, geographical proximity between cities, and proximity of urban innovation capacity. Patent cooperation tends to concentrate on the regions with large patent output; Zhang Ruofan [22] found that the inter-city cooperation network of the Guangdong-Hong Kong-Macao Greater Bay Area presented a significant marginal core structure.…”
Section: Inter-city Patent Cooperation In Beijing-tianjin-hebei Regionmentioning
confidence: 99%
“…Presently, urban areas enjoy ample and at times excessive access to these services, while impoverished regions, especially in public healthcare and social security, still require substantial improvements. Moreover, economic development plays a crucial role in shaping the supply pattern of basic public services, creating a distinct east-to-west ladder-shaped distribution with significant regional variations ( 23 ). The economically advanced eastern region benefits from substantial public finance investment and a robust financial system, resulting in a more robust provision of basic public services compared to less developed areas.…”
Section: Hypothesismentioning
confidence: 99%
“…Nonetheless, some researchers have pointed out a decline in the equalization of basic public services in China, with transfer payments proving insufficient in promoting equalization ( 22 ). Assessing the performance of basic public services, scholars have observed regional disparities in efficiency across 30 Chinese provinces from 2006 to 2019, showing a pattern of “high in the east and low in the west” ( 23 ). Contrasting this, in Germany, property rights and organizational structures significantly impact public service provision, with public ownership proving more efficient than mixed or private ownership ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…From 2012 to 2015 (fluctuation decline stage), on the one hand, some countries were in a period of rapid economic development [ 50 , 51 ], and the total energy consumption and carbon emissions increased sharply [ 52 ]. During the study period, the energy consumption of fossil fuels accounted for more than 95% of the total energy consumption in Algeria, Oman, Kazakhstan, Saudi Arabia, Malaysia and other countries; on the other hand, some countries have relatively more fossil fuels such as coal resources, petroleum resources, and natural resources [ 53 , 54 ]. With the large-scale use of fossil energy, the energy structure is unreasonable [ 55 ].…”
Section: Spatial and Temporal Evolution Characteristics Of Global Ceementioning
confidence: 99%